Perlindungan Hukum bagi Pemilik Hak atas Tanah yang Telah Dialihkan dan Dibebankan Hak Tanggungan - Marsya Duni Puteri (Jurnal Hukum Lex Generalis, 2025)
In the transfer of land rights through the making of land sales and purchases, criminal acts of forgery of documents in Article 263 of the Criminal Code to Article 266 of the Criminal Code. The problem in this study, regarding the position of the transfer and the imposition of mortgage rights after the Criminal Court Decision which decides the perpetrator is proven guilty of committing the crime of entering false information into an authentic deed and efforts to return the land object that has been burdened with mortgage rights as a form of legal protection for land rights owners who are unaware of the transfer and imposition of land rights after the court decision. The results of the study explain that the position of the transfer and imposition of mortgage rights can be null and void by law on the basis of not fulfilling the requirements of a lawful cause and the material requirements for making a deed. The form of legal protection for land rights owners who are unaware of the transfer and imposition of land rights after the court decision. The results of the study explain that the position of transfer and burden is to file a lawsuit for Cancellation of the Sale and Purchase Deed and cancellation of the ownership certificate issued by the National Land Agency to the State Administrative Court as well as an application for cancellation of the SHM to the BPN Based on a Court Decision that has Permanent Legal Force.